(untitled) (Revista de Estudios Europeos, 2026)
This article analyzes the representation of the 27 countries of the European Union in the European Parliament. It explicitly establishes that, in the current legislative period, Spain is underrepresented. This is due to three reasons. The first is that the seats for the 2024-2029 period were distributed through political negotiations. The second is that the population data used in those negotiations were from two years prior to the elections. Third, no effort was made in the distribution to ensure that the ratios of inhabitants to seats for each country decreased in a similar way to the decrease in populations when moving from the most populated country to the least populated. All of this means that the current distribution of seats in the European Parliament violates the downward proportionality required by the Treaty on European Union, with respect to the populations in 2023. Here, the rules for this distribution are applied and a formula is provided that allows the seat quota for each country to be calculated based on the states’ populations, thus avoiding negotiations to determine the composition of the European Parliament each time elections are looming. Furthermore, this seat calculation can be made at the time of calling the elections, allowing the most recent official population figures available at the time of the call to elections to be used. The indicated formula results in a distribution of seats that always complies with all the restrictions of the Treaty on European Union. It is also proposed that the maximum limit of 96 seats for all states should not discriminate against the most populous country. This is achieved by reducing the size of the European Parliament. Currently, considering the 2023 populations, the size would have been 701 seats instead of 720.